Model Analisis Kualitas Pelayanan Terhadap Word Of Mouth Melalui Komitmen Relasional Dan Kepuasan Mahasiswa Sebagai Variabel Intervening (Studi Pada Mahasiswa Universitas Mathla’ul Anwar Banten) - Supartini, Sri; Lutfi, Lutfi (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2020)
This paper was conducted to examine the effect of service quality to word of mouth (WOM) and relational commitment to student satisfaction as an interevening variable. The study was conducted at students of Mathla'ul Anwar University, Banten. The number of samples in this study were 97 students with a propionate stratified random sampling method, which means that the sampling was carried out proportionally to each stratum in the population, in this case students from each faculty at Mathla'ul Anwar University, Banten. Data analysis method used in this research was Smart PLS 3.2.8 software. The results of this study indicated that (1) Service quality has a positive effect on students satisfaction, (2) Service quality has a positive effect to Word of Mouth, (3) Service quality has no effect on relational commitment, (4) Students satisfaction have no effect to word of mouth, (5) Students satisfaction has a positive effect to relational commitment, (6) Relational commitment is affected to word of mouth.